PENERAPAN TERAPI PENERIMAAN DAN KOMITMEN PADA KLIEN KETIDAKPATUHAN MINUM OBAT DI RUMAH SAKIT JIWA - Waluyo, Agus; Yani S. Hamid, Achir (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Schizophrenia is a form of chronic mental disorders, It took a long time for the healing process, many of the clients stop taking their drugs. The duration of treatment programs and drug side effects as one cause for non-compliance with the clients treatment program. The purpose of this scientific paper was to describe the nursing case management of the clients medication non-compliance behavior using Interpersonal Peplau and Stress Adaptation Stuart Theories at Dewi Amba nursing ward of dr. H. Marzoeki Mahdi Hospital, Bogor. Acceptance and commitment therapy was conducted 17 clients. The results obtained Acceptance and Commitment Therapy effectively improve client acceptance and commitment to the medication program therapy. Acceptance and Commitment Therapy is recommended as therapy nursing specialists, provided to the client with a mental disorder clients who have a problem on medication non-compliance.Keywords: Medication non-compliance, Acceptance and Commitment Therapy, Peplau and Stuart Theories.